2001
DOI: 10.1106/ykdm-px8k-nf6q-l7fk
|View full text |Cite
|
Sign up to set email alerts
|

Computer Modeling and FEA Simulation for Composite Single Fiber Pull-Out

Abstract: Using state-of-the-art computer-aided technologies, particularly CAD and integrated CAD/FEA technique to model and simulate the composite, the single-fiber pull-out problem is presented. The capability and effectiveness of using enabled CAD to generate solid modeling based composite fiber/matrix heterogeneous assembly and its application with the seamless integration of CAD/FEA to simulate fiber pull-out mechanisms and effects of material and geometric variation on stresses in fiber and matrix are demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Advanced CAD software, Pro/Engineer, is used to construct the inner fiber (cylinder) and concentric outer (matrix) cylinder as individual fiber and matrix parts which are assembled to form a composite to represent a fiber pull-out CAD model. Only a quarter of the pull-out test was modeled using Pro Engineer as the state of stresses will be symmetrical which is in line with the work carried out by Sun and Lin [10]. Then, the Pro/Engineer model was converted into a Pro/ MECHANICA model for finite element analysis.…”
Section: Simulation Computer Modeling and Analysismentioning
confidence: 85%
“…Advanced CAD software, Pro/Engineer, is used to construct the inner fiber (cylinder) and concentric outer (matrix) cylinder as individual fiber and matrix parts which are assembled to form a composite to represent a fiber pull-out CAD model. Only a quarter of the pull-out test was modeled using Pro Engineer as the state of stresses will be symmetrical which is in line with the work carried out by Sun and Lin [10]. Then, the Pro/Engineer model was converted into a Pro/ MECHANICA model for finite element analysis.…”
Section: Simulation Computer Modeling and Analysismentioning
confidence: 85%
“…The study of the composite simulation by FEA packages has been reported, extensively, in literature by various investigators [24][25][26][27][28]. The present problem is modeled as a core cylinder representing fiber attached with a hollow cylinder of matrix material to form a single representative volume element bonded at the surfaces between fiber and matrix as shown in Figure 2(a) without considering interphase, while core cylinder representing fiber attached with hollow cylinder of interphase which is further attached with a hollow cylinder of matrix material to form a single representative volume element bonded at the surfaces between fiber and interphase and interphase and matrix, as shown in Figure 2(b).…”
Section: Simulation Methodologymentioning
confidence: 99%
“…On the other hand, the continuum-mechanics based approach is able to depict the contact and friction between materials and tools since the material property can be considered in the numerical calculation. In the micro-or meso-scale continuum models [7][8][9][10], fibers in yarns (or yarn structures in a unit cell) are modeled as three dimensional solid elements and the representative material properties are predicted. However, such micro-or meso-scale methods require the enormous computation cost.…”
Section: Introductionmentioning
confidence: 99%